Research Progress on Metal-Organic Frameworks as Drug Carriers - Raut, Dipanwita; Park, David (Journal of Green Energy and Environmental Engineering, 2024)
Metal–organic frameworks (MOFs) are crystalline hybrids in which metal nodes or clusters are stitched into ordered nets by multitopic organic linkers. Their crystalline lattices combine ultra-large surface areas, mesoporous channels and engineerable metrics, while their room-temperature or solvothermal syntheses are remarkably straightforward. These features have propelled MOFs to the forefront of drug-delivery research, yet residual metal leaching and ligand degradation still raise cytotoxic red flags. Cyclodextrin-based MOFs (CD-MOFs)—built only from γ-cyclodextrin rings and biogenic K⁺ ions—have recently been shown to bypass this bottleneck, offering an intrinsically benign, biocompatible platform for pharmaceutical applications. They can address the practical application shortcomings of MOFs in drug delivery, effectively improve the stability of guest drug molecules, and enhance efficacy, making them highly potential drug carriers. This article will review the synthesis and safety of CD-MOFs, as well as their advantages and limitations as drug carriers.